SPX family response to low phosphorus stress and the involvement of ZmSPX1 in phosphorus homeostasis in maize - Luo, Bowen; Sahito, Javed Hussain; Zhang, Haiying; Zhao, Jin; Yang, Guohui; Wang, Wei; Guo, Jianyong; Zhang, Shuhao; Ma, Peng; Nie, Zhi; Zhang, Xiao; Liu, Dan; et al. (Frontiers in Plant Science, 2024)
Phosphorus (P) is a crucial macro nutrient for plant growth and development, and low-Pi stress poses a significant limitation to maize production. While the role of the SPX domain in encoding proteins involved in phosphate (Pi) homeostasis and signaling transduction had been extensively studied in other model plants, the molecular and functional characteristics of the SPX gene family members in maize remain largely unexplored. In this study, we identified six SPX members, and the phylogenetic analysis of ZmSPXs revealed a close relationship with SPX genes in rice. The promoter regions of ZmSPXs were abundant in biotic and abiotic stress-related elements, particularly associated with various hormone signaling pathways, indicating potential intersections between Pi signaling and hormone signaling pathways. Additionally, ZmSPXs displayed tissue-specific expression patterns, with significant and differential induction in anthers and roots, and were localized to the nucleus and cytoplasm. The interaction between ZmSPXs and ZmPHRs was established via yeast two-hybrid assays. Furthermore, overexpression of ZmSPX1 enhanced root sensitivity to Pi deficiency and high-Pi conditions in Arabidopsis thaliana. Phenotypic identification of the maize transgenic lines demonstrated the negative regulatory effect on the P concentration of stems and leaves as well as yield. Notably, polymorphic sites including 34 single nucleotide polymorphisms (SNPs) and 7 insertions/deletions (InDels) in ZmSPX1 were significantly associated with 16 traits of low-Pi tolerance index. Besides, significant sites were classified into 5 haplotypes and haplotype5 can enhance biomass production by promoting root development. Taken together, our results suggested that ZmSPX family members possibly play a pivotal role in Pi stress signaling in plants via interacting with ZmPHRs. Significantly, ZmSPX1 was involved in the Pi-deficiency response verified in transgenic Arabidopsis and can affect the Pi concentration of maize tissues and yield. This work lays the groundwork for deeper exploration of the maize SPX family and could inform the development of maize varieties with improved Pi efficiency.